Carbon Emission Reduction Effects of Green Credit Policies: Empirical Evidence From China - Qin, Jiahong; Cao, Jianhua (Frontiers in Environmental Science, 2022)
This paper employs the Green Credit Guidelines as green financial policy to investigate whether the implementation of green credit has contributed to the low-carbon economic development. The difference-in-differences method (DID) is then applied to estimate the emission reduction effects. The paper found that green financial policy has effectively reduced pollution and energy consumption in high pollution and high energy consuming industries. As a means of verifying the reliability of the results, propensity score matching difference-in-differences (PSM-DID) applies the match kernels and radius method before the DID. Furthermore, this paper explored the regional and industry heterogeneity in incremental carbon emission reductions. This is the first paper to use Guidelines to measure green finance, in order to achieve indicator innovation and provide corresponding policy advice. To achieve carbon neutrality, the government must strengthen the implementation of green credit policy and create a green financial environment tailored to local needs.